Digital Environmentalism: The Role of Social Media in Shaping Climate Awareness and Action - Deepak Kumar Saini; Arzoo Rana (Indonesian Journal of Social and Environmental Issues (IJSEI), 2025)
Climate change represents one of the most pressing challenges facing humanity in the 21st century. This review examines the multifaceted role of social media in contemporary environmental movements, exploring how digital platforms have transformed climate communication, analyzing the effectiveness of digital campaigns, and addressing the challenges and limitations of online environmental activism. Through a comprehensive synthesis of recent scholarship on digital environmentalism, this article provides insights into both the potential and pitfalls of social media as a tool for climate action. The findings reveal that social media serves as a powerful tool for raising climate awareness and mobilizing action when used strategically, while also facing significant limitations, including misinformation, the digital divide, and platform dependency. The review concludes that hybrid approaches combining digital and traditional organizing methods, alongside intentional efforts to bridge accessibility gaps and advance environmental justice, represent the most promising path forward for effective climate action.